Importance of myorelaxation in patients with severe coma - Usmonov U.R (Genius Journals, 2023)
In recent years, in patients with severe head injuries, the symptoms of ALV are observed more often, and the need for artificial respiration is observed more often. In this article, parameters of a total of 65 patients during artificial respiration were monitored in the ALV device. In 40 of the total patients, tracheal intubation and ALV apparatus were used to create an optimal environment during artificial respiration. The reduction of resistance to the ALV apparatus led to the normalization of intracranial pressure and the normalization of the amount of oxyhemoglobin in the intracranial pressure. Hypotonia and deepening of consciousness were observed in 25 patients
Keywords: ALV; myorelaxation; oxyhemoglobin